Methods for detection of biofilms in bacteria and fungi - Bhattacharya, Sayan (Eastern Journal of Medical Sciences, 2023)
Biofilms are layer-like structures formed by microorganisms and extracellular matrix produced by them on indwelling devices. Biofilms can also readily form over catheters and devices like prosthetic valves. They help in conferring drug resistance to the biofilm-associated cells and help the microbes escape from antimicrobials as well as the immune defense of the host. There are also many methods of detecting microbial biofilms in vitro, which will be reviewed in this article.